Mice with endogenous TDP‐43 mutations exhibit gain of splicing function and characteristics of amyotrophic lateral sclerosis. (15th May 2018) - Fratta, Pietro; Sivakumar, Prasanth; Humphrey, Jack; Lo, Kitty; Ricketts, Thomas; Oliveira, Hugo; Brito‐Armas, Jose M; Kalmar, Bernadett; Ule, Agnieszka; Yu, Yichao; Birsa, Nicol; Bodo, Cristian; et al.
Abstract: TDP‐43 (encoded by the gene TARDBP ) is an RNA binding protein central to the pathogenesis of amyotrophic lateral sclerosis (ALS). However, how TARDBP mutations trigger pathogenesis remains unknown. Here, we use novel mouse mutants carrying point mutations in endogenous Tardbp to dissect TDP‐43 function at physiological levels both in vitro and in vivo . Interestingly, we find that mutations within the C‐terminal domain of TDP‐43 lead to a gain of splicing function. Using two different strains, we are able to separate TDP‐43 loss‐ and gain‐of‐function effects. TDP‐43 gain‐of‐function effects in these mice reveal a novel category of splicing events controlled by TDP‐43, referred to as "skiptic" exons, in which skipping of constitutive exons causes changes in gene expression. In vivo, this gain‐of‐function mutation in endogenous Tardbp causes an adult‐onset neuromuscular phenotype accompanied by motor neuron loss and neurodegenerative changes. Furthermore, we have validated the splicing gain‐of‐function and skiptic exons in ALS patient‐derived cells. Our findings provide a novel pathogenic mechanism and highlight how TDP‐43 gain of function and loss of function affect RNA processing differently, suggesting they may act at different disease stages. Synopsis: Point mutations within the low complexity C‐terminal domain of TDP‐43 induce phenotypes resembling amyotrophic lateral sclerosis and motor neuron disease in mice. Molecularly, these mutations induce a novel gain of splicing activity leading to skipping of certain constitutive exons, a phenomenon designated as "skiptic" exons here. Two new mouse lines express endogenous TDP‐43 with mutations in either the RNA‐recognition motif or in the C‐terminal low complexity domain. Mice carrying a C‐terminal TDP‐43 mutation develop a progressive neuromuscular phenotype accompanied by loss of motor neurons. Motor neuron degeneration occurs in the absence of TDP‐43 splicing loss‐of‐function. Endogenous TDP‐43 C‐terminal mutations induce gain‐of‐function splicing activity. TDP‐43 gain‐of‐function activity leads to the skipping of constitutive exons, referred to as "skiptic" exons. Abstract : Two new TDP‐43 mutant mouse models reveal that splicing gain‐of‐function contributes to motor neuron degeneration via increased skipping of constitutive exons.